A non-Ohmic normally-off GaN monolithic bidirectional switch with MIS field effect schottky tunnel junction. (September 2017) - Shi, Yijun; Chen, Wanjun; Zhou, Qi; Zhang, Bo
Abstract: A non-Ohmic normally-off GaN Monolithic bidirectional switch (MBS) with two metal-insulator-semiconductor field-effect schottky tunnel junctions is proposed and investigated by TCAD sentaurus. The MBS exhibits normally-off operation on account of the thick tunnel barrier at schottky-source and schottky-drain electrodes, whose effective thickness is controlled by two insulated gates next to source and drain. A positive gate bias can pull down the conduction band and result in a thin tunnel barrier with high tunneling current, while a zero gate bias brings about a thick barrier effectively suppressing the tunneling current. The simulated results show that the proposed MBS can deliver a low off-state current of 10 μA and a small on-state voltage of 3.55 V at the same time. And compared with the conventional Ohmic-contact MBS, the proposed MBS does not show any degeneration in on-state loss. Moreover, the absence of Au-based Ohmic process and high temperature annealing process enables the proposed MBS with CMOS compatibility and low thermal budget. Highlights: The absence of Au-based Ohmic process enables the proposed MBS with CMOS compatibility. The device can be fabricated in low temperature. The high temperature process of Ohmic annealing has been revealed as the primary cause for the formation of nitrogen deficiency and oxidation of bare (Al)GaN surface, affecting the electrostatic boundary conditions on the 2DEG at the AlGaN/GaN interface and leading to the degradation of dynamic performance of GaN-based HEMTs. So the low-thermal-budget process is necessary and meaningful. Low off-state leakage of the proposed MBS can be obtained by decreasing the remained thickness under gate region.